Genome sequence dataset of Bacillus altitudinis strain ST14 isolated from Tunggak River in Gebeng Industrial Park, Kuantan, Pahang - Abdul Aziz, Asmadamia; Zulbahri, Azuan Syafiq; Sharif, Mohd Faez; Mohamad, Mohd Azrul Naim; Gan, Han Min; Azizan, Nur Hafizah (Elsevier Inc., 2022)
Bacillus sp. has been reported to be involved in the biodegradation of various hydrocarbon pollutants which can potentially be useful in cleaning up hydrocarbon pollutants. Here we report the draft genome of Bacillus altitudinis strain ST14 isolated from Tunggak river, Gebeng, Kuantan, an area in close proximity to industrial activities. Genome sequencing was conducted using Illumina NovaSEQ 6000 technology. Structural genes in the genome were described, including rRNAs, tRNAs, and ncRNAs. Bacillus altitudinis strain ST14 was sequenced with a length of 3,801,811 bp containing 3,891 coding sequences (CDS). Functional gene annotation reported the presence of six enzymes involved in the degradation of aromatic compounds often found in hydrocarbon pollutants.